2019
DOI: 10.32668/jitek.v7i1.194
|View full text |Cite
|
Sign up to set email alerts
|

Efikasi Diri Berhubungan dengan Kepatuhan Manajemen Diri pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Buleleng III

Abstract: Diabetes mellitus is a group of metabolic diseases with characteristics of hyperglycemia that occur due to abnormal insulin secretion and insulin performance. Prevention of the occurrence of DM complications can be done by obediently doing good self-management behavior. Self-management compliance of good diabetes mellitus can achieve success if individuals have the knowledge, skill, and self-efficacy to manage diabetes mellitus. Self-efficacy determines how a person feels, thinks, motivates himself, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…On the contrary, when selfefficacy is good, self-care behavior will be more obedient. This opinion is in line with the research of Handayani, Putra & Laksmi (2019) which reported that the higher the self-efficacy, the higher the compliance level in carrying out self-management of diabetic people. As a result, hopes or desires to improve health status or recover were more significant.…”
Section: Self-efficacysupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, when selfefficacy is good, self-care behavior will be more obedient. This opinion is in line with the research of Handayani, Putra & Laksmi (2019) which reported that the higher the self-efficacy, the higher the compliance level in carrying out self-management of diabetic people. As a result, hopes or desires to improve health status or recover were more significant.…”
Section: Self-efficacysupporting
confidence: 89%
“…According to Handayani, Putra & Laksmi (2019), self-efficacy was the essential element to increase compliance in diabetic individuals in terms of self-management or self-care. The formation of a person's self-efficacy is obtained from experienced others by fostering self-confidence to affect the behavior to carry out well-planned tasks and goals, such as self-care compliance.…”
Section: Self-efficacymentioning
confidence: 99%
“…Berdasarkan data didapatkan kurang dari separuh (37,3%) responden berpendidikan SMA sehingga menurut Niven (2012), seseorang yang berpendidikan SMA mempengaruhi kepatuhan minum obat karena memiliki pengetahuan yang cukup baik terhadap dosis obat yang diminum sesuai dengan resep dokter. Sejalan dengan beberapa hasil riset lain yang menyebutkan bahwa sebagian besar latar belakang pendidikan pasien DM di Indonesia adalah pendidikan dasar (SD, SMP dan SMA) (Padmayani, 2022;Saputri, 2021). Semakin tinggi pendidikan seseorang maka dapat berdampak pada tingkat pengetahuannya (Nazriati, Pratiwi dan Restuastuti, 2018).…”
Section: Gambaran Karakteristik Demografi Responden Dmunclassified